(untitled) (Conferencea, 2022)
Until now, the problem of rhinosinusitis (RS) has not lost its relevance in pediatrics and otorhinolaryngology, which is associated with a continuing increase in the incidence. According to different authors, from 5 to 15% of the adult population and about 5% of children suffer from RS in one form or another [1]. RS in children is defined as an inflammation of the mucous membrane of the nose and paranasal sinuses (PS), manifested by two or more symptoms, one of which is nasal congestion/difficulty in nasal breathing or discharge from the nose (outwards, into the nasopharynx), as well as facial pain or cough. In addition, RS is characterized by the presence of certain endoscopic signs (polyps in the nasal cavity, mucopurulent discharge mainly from the middle nasal passage, mucosal edema mainly in the middle nasal passage), as well as CT signs of changes in the mucous membrane of the osteomeatal complex or PS